Hubungan Tingkat Pengetahuan tentang Perubahan Fisiologis dan Psikologis Fase Premenopouse terhadap Tingkat Kecemasan pada Pralansia - Zuliana .; Ennimay .; Yecy Anggreny (Jurnal Kesehatan Komunitas, 2014)
Knowledge was the resulted of human sensing that strongly influenced by the intensity of attention and object perception. Anxiety was a felt of fear that was not clear and not supported by the situation. This study aims to determine the relationship betwen level of knowledge about physiological and psychological changes in premenopausal phase and level of anxiety in pre-old woman. This research was quantitative design with cross-sectional. Total sample in this study are 90 premenopausal women who experience pre-old women at Working Area of Health Public Center in Pekanbaru, used purposive sampling technique. Data was analyzed with univariate and bivariate frequency distributions with chi-square test. The results showed an relationship between the level of knowledge about the physiological and psychological changes in premenopausal phase and the level of anxiety in pre-old women with p value = 0.000 (p <0.1). This study recommended that additional studies by increasing the number of samples so that the whole population can be represented.